2002
DOI: 10.1104/pp.001925
|View full text |Cite
|
Sign up to set email alerts
|

Cold-Regulated Cereal Chloroplast Late Embryogenesis Abundant-Like Proteins. Molecular Characterization and Functional Analyses

Abstract: Cold acclimation and freezing tolerance are the result of complex interaction between low temperature, light, and photosystem II (PSII) excitation pressure. Previous results have shown that expression of the Wcs19 gene is correlated with PSII excitation pressure measured in vivo as the relative reduction state of PSII. Using cDNA library screening and data mining, we have identified three different groups of proteins, late embryogenesis abundant (LEA) 3-L1, LEA3-L2, and LEA3-L3, sharing identities with WCS19. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
147
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 180 publications
(153 citation statements)
references
References 56 publications
5
147
0
1
Order By: Relevance
“…WCS19 (encoding for a wheat LEA3-L2 protein) constitutively expressed in Arabidopsis resulted in significant freezing tolerance and resistance to photoinhibition (Ndong et al, 2002). Under in vitro conditions, an algal (Chlorella vulgaris) LEA 3 protein diminished the freeze-induced damage of the enzyme lactate dehydrogenase (Honjoh et al, 2000).…”
Section: Group 3 Leamentioning
confidence: 99%
“…WCS19 (encoding for a wheat LEA3-L2 protein) constitutively expressed in Arabidopsis resulted in significant freezing tolerance and resistance to photoinhibition (Ndong et al, 2002). Under in vitro conditions, an algal (Chlorella vulgaris) LEA 3 protein diminished the freeze-induced damage of the enzyme lactate dehydrogenase (Honjoh et al, 2000).…”
Section: Group 3 Leamentioning
confidence: 99%
“…Although many researchers have indicated that transgenic plants expressing LEA proteins under the control of regulated or constitutive promoters showed tolerant phenotypes under drought, high salinity or freezing stress (Xu et al 1996;Sivamani et al 2000;NDong et al 2002;Babu et al 2004;Puhakainen et al 2004;Fu et al 2007;Lal et al 2008;Xiao et al 2007;Dalal et al 2009), this ''gain-of-function'' approach may not sufficiently reflect their direct participation in the plant's adjustment or adaptation to these stress conditions but rather their potential to confer tolerance when ectopically expressed (Olvera-Carrillo et al 2010). In recent years, a reverse genetics technology called VIGS has being employed by many researchers (Kumagai et al 1995;Ratcliff et al 1997;Baulcombe 1999;Liu et al 2002).…”
Section: Vigs a Practicable Methods For Gene Functional Analysis Of Tmentioning
confidence: 99%
“…Late embryogenesis abundant (LEA) proteins are an ABA-dependent protein family. The proteins can be detected in embryo and tissue with water stress (NDong et al 2002;Grelet et al 2005;Shih et al 2010). Because OsLEA1 can be detected in rice callus and is an ABA-induced gene (Shih et al 2010), the gene expression could present as the endogenous ABA level.…”
Section: Introductionmentioning
confidence: 99%